2007
DOI: 10.1021/jf0700576
|View full text |Cite
|
Sign up to set email alerts
|

δ1-Pyrroline-5-carboxylic Acid Formed by Proline Dehydrogenase from theBacillus subtilisssp. natto Expressed inEscherichia colias a Precursor for 2-Acetyl-1-pyrroline

Abstract: Proline dehydrogenase (PRODH) catalyzes the biosynthesis of Delta1-pyrroline-5-carboxylic acid (P5C). The Bacillus subtilis subsp. natto gene for the proline dehydrogenase (BnPRODH) was cloned and expressed in Escherichia coli. Nucleotide sequence analysis of the clone revealed an open-reading frame that encodes 302 amino acid polypeptide with a calculated molecular mass of 34.5 kDa. The deduced amino acid sequence showed sequence similarity to bacterial PRODH and PutA of E. coli. The BnPRODH gene was cloned i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…This also confirms non-enzymatic formation of 2AP as also suggested by other researchers (Chen et al 2008). Methylglyoxal was identified as the carbon source for 2AP (Huang et al 2007(Huang et al , 2008. They synthesised 2AP non-enzymatically at room temperature simply by stirring mixture of P5C (Δ 1 -pyrroline-5-carboxylic acid) and Methylglyoxal for 30 min.…”
Section: Substrate Specificity and Activity Of Badh2supporting
confidence: 82%
See 1 more Smart Citation
“…This also confirms non-enzymatic formation of 2AP as also suggested by other researchers (Chen et al 2008). Methylglyoxal was identified as the carbon source for 2AP (Huang et al 2007(Huang et al , 2008. They synthesised 2AP non-enzymatically at room temperature simply by stirring mixture of P5C (Δ 1 -pyrroline-5-carboxylic acid) and Methylglyoxal for 30 min.…”
Section: Substrate Specificity and Activity Of Badh2supporting
confidence: 82%
“…It was found that the loss of function of enzyme betaine aldehyde dehydrogenase 2 (BADH2) is responsible for the accumulation of γ-aminobutyraldehyde (GABald)/Δ 1 -pyrroline; the immediate precursor of 2AP. The addition of acetyl group via methylglyoxal; a product of sugar degradation takes place in Δ 1 -pyrroline to form 2AP (Huang et al 2007(Huang et al , 2008. The synthesis of 2AP in aromatic rice as well as plants like P. amaryllifolius and V. glabra is constitutive in all aerial parts however, in B. latifolia the synthesis of 2AP takes place only in flowers (fleshy corolla), that too at mature stage (Wongpornchai et al 2003;Lorieux et al 1996;Buttery et al 1983a).…”
Section: Introductionmentioning
confidence: 99%
“…SPP1 plating in knockout strains carrying a complementing allele of the relevant gene that is expressed ectopically under an inducible P xyl promoter at the amyE locus are shown labeled as complement. The SPP1 plaque phenotype on the putB found to be necessary for efficient phage infection fall into three classes: (i) genes from the yuk operon (yukE, yukD, yukC, yukB, and yueB) coding for components of the Esat-6-like secretion system (40); (ii) protein synthesis (efp [41]); (iii) intermediary metabolism (ycgM [42,43]). As it was elegantly demonstrated by the groups of M. A. Santos and C. São-José, YueB and other proteins encoded by the yuk operon are required for phage SPP1 irreversible binding to the B. subtilis cell surface and are possibly involved in postadsorption events, such as phage genome transfer to the host cell cytoplasm (13,32,40).…”
Section: Resultsmentioning
confidence: 99%
“…YcgM is a proline dehydrogenase, the first enzyme of the pathway for oxidation of proline to glutamate (42,43). Its function has been demonstrated in B. subtilis, and the name of the gene has been changed to putB (43).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Huang et al (2008) reported higher level of MG in scented rice calli than that of non-scented rice calli. Huang et al (2007) demonstrated that MG reacts with P5C, to form 2AP. In the present study, higher levels of MG might be contributing towards higher levels of 2AP in SMB.…”
Section: Biosynthetic Mechanism Of 2apmentioning
confidence: 99%